2019
DOI: 10.1111/vop.12698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial culture results collected via direct corneal ulcer vs conjunctival fornix sampling in canine eyes with presumed bacterial ulcerative keratitis

Abstract: ObjectiveTo compare aerobic bacterial culture results between samples obtained from the corneal ulcer versus lower conjunctival fornix in eyes with presumed bacterial ulcerative keratitis.Animals studiedFifty five client‐owned dogs diagnosed with ulcerative keratitis.ProceduresOphthalmic examinations were performed on each dog including slit‐lamp biomicroscopy and indirect ophthalmoscopy. Microbial swabs were collected by direct sampling of the infected corneal ulcer as well as the lower conjunctival fornix, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
6
18
1
Order By: Relevance
“…These findings are generally in agreement with other canine studies across the globe ( 2 , 3 , 9 11 ), with subtle geographic differences such as a lower prevalence of Staphylococcus species in Australia ( 8 ) or a relatively higher prevalence of Streptococcus species in the Midwestern United States (present study) compared to other locations ( 6 , 7 ). Staphylococcus pseudintermedius was the most common Staphylococcus species (26.7% of all isolates), as recognized in most canine reports ( 2 , 3 , 7 , 10 , 11 ), followed by non-specified Coagulase-negative Staphylococcus species (3%) and Staphylococcus epidermidis (0.6%). Surprisingly, Staphylococcus aureus only accounted for 0.4% of isolates in the present study, while it had previously been reported as more prevalent in canine bacterial keratitis ( 6 , 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are generally in agreement with other canine studies across the globe ( 2 , 3 , 9 11 ), with subtle geographic differences such as a lower prevalence of Staphylococcus species in Australia ( 8 ) or a relatively higher prevalence of Streptococcus species in the Midwestern United States (present study) compared to other locations ( 6 , 7 ). Staphylococcus pseudintermedius was the most common Staphylococcus species (26.7% of all isolates), as recognized in most canine reports ( 2 , 3 , 7 , 10 , 11 ), followed by non-specified Coagulase-negative Staphylococcus species (3%) and Staphylococcus epidermidis (0.6%). Surprisingly, Staphylococcus aureus only accounted for 0.4% of isolates in the present study, while it had previously been reported as more prevalent in canine bacterial keratitis ( 6 , 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, Staphylococcus aureus only accounted for 0.4% of isolates in the present study, while it had previously been reported as more prevalent in canine bacterial keratitis ( 6 , 9 ). Streptococcus canis (12%) and Pseudomonas aeruginosa (7.5%) were the most common species cultured for each respective genus, consistent with previous reports ( 3 , 8 , 10 , 11 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…complex ulcers in dogs indicate Staphylococcus spp., St reptococcus spp., Pasteurella multocida, Pseudomonas aeruginosa, Corynebacterium spp., Neisseria spp., and Escherichia coli. 8 S pseudintermedius, beta-hemolytic Streptococcus spp., P aeruginosa, and methicillin-resistant Staphylococcus organisms were the most common. 8,10 Chronic ofloxacin use over a three-week period following cataract surgery has been described to result in a change in the predominant ocular bacterial population from S pseudintermedius to coagulase-negative Staphylococcus spp., an increase in resistance to ofloxacin, and an overall increase in bacterial load.…”
mentioning
confidence: 99%